2022
DOI: 10.1016/j.jvoice.2020.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Voice Rehabilitation After Open Partial Horizontal Laryngectomy Through the Proprioceptive Elastic Method (PROEL): A Preliminary Study

Abstract: Objective. The aim was to investigate the efficacy of the Proprioceptive Elastic Method (PROEL) in the rehabilitation of the substitution voice after open partial horizontal laryngectomy (OPHL). Study Design. Prospective outcome study.Methods. 15 patients surgically treated by OPHL type II or type III for laryngeal cancer were recruited (experimental group). Each patient underwent a specific program of voice rehabilitation based on the PROEL method with the same speech and language pathologist. Acoustic-aerody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
2
Order By: Relevance
“…6,[15][16][17] Nevertheless, a satisfactory level of oral communication is generally achieved through a substitution voice. 18,19 Swallowing recovery after open partial laryngectomies is surely a challenging process and has been widely investigated by many authors. 8,[20][21][22][23] Swallowing function is always severely impaired immediately after surgery, but generally recovers in about 6 months, with patients finally reaching a free oral diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[15][16][17] Nevertheless, a satisfactory level of oral communication is generally achieved through a substitution voice. 18,19 Swallowing recovery after open partial laryngectomies is surely a challenging process and has been widely investigated by many authors. 8,[20][21][22][23] Swallowing function is always severely impaired immediately after surgery, but generally recovers in about 6 months, with patients finally reaching a free oral diet.…”
Section: Discussionmentioning
confidence: 99%
“…Voice quality is usually well preserved after Type I OPHLs, since vocal folds are spared, while is highly and similarly deteriorated after Type II and Type III OPHLs 6,15–17 . Nevertheless, a satisfactory level of oral communication is generally achieved through a substitution voice 18,19 . Swallowing recovery after open partial laryngectomies is surely a challenging process and has been widely investigated by many authors 8,20–23 .…”
Section: Discussionmentioning
confidence: 99%
“…Uma menor tensão muscular no corpo produz uma maior elasticidade do sistema fonatório, levando a um estado ecológico máximo. Pesquisas com delineamento do tipo intervenção antes-após evidenciou melhora da qualidade vocal de pacientes com disfonia funcional (39) e um estudo quasi-experimental a melhora da qualidade da voz de pacientes submetidos a laringectomia parcial horizontal (40) .…”
Section: Técnicas Vocais Tradicionais Na Reabilitação Vocalunclassified
“…Reconhece-se ainda que as abordagens tradicionais de reabilitação vocal produzem efeito não somente sobre a voz, mas sobre a competência comunicativa e aspectos emocionais dos pacientes (6) . Tanto métodos específicos, como o LSVT, para indivíduos com Doença de Parkinson (9)(10)(11) , como holísticos, como o PROEL (39,40) produzem efeitos positivos imediatos e no curto-prazo. A maior concentração de evidências de qualidade sobre os efeitos da intervenção fonoaudiológica concentram-se sobre as abordagens tradicionais de reabilitação.…”
Section: Comentáriosunclassified
“…Makeieff et al [1] have shown that after such surgery, voice is a significant quality of life factor. Fantini et al [2] studied the rehabilitation of the substitution voice after open partial horizontal laryngectomy and identified the need for larger groups of patients to research voice discrepancy and rehabilitation. Schindler et al [3] reported that the findings showed a highly dysphonic voice after laryngectomies.…”
Section: Introductionmentioning
confidence: 99%